Diagnosis, Treatment, and Outcome in Patients with Bleeding Peptic Ulcers and Helicobacter pylori Infections. (30th June 2014) - Huang, Ting-Chun; Lee, Chia-Long
Abstract : Upper gastrointestinal (UGI) bleeding is the most frequently encountered complication of peptic ulcer disease. Helicobacter pylori ( Hp ) infection and nonsteroidal anti-inflammatory drug (NSAID) administration are two independent risk factors for UGI bleeding. Therefore, testing for and diagnosing Hp infection are essential for every patient with UGI hemorrhage. The presence of the infection is usually underestimated in cases of bleeding peptic ulcers. A rapid urease test (RUT), with or without histology, is usually the first test performed during endoscopy. If the initial diagnostic test is negative, a delayed 13 C-urea breath test (UBT) or serology should be performed. Once an infection is diagnosed, antibiotic treatment is advocated. Sufficient evidence supports the concept that Hp infection eradication can heal the ulcer and reduce the likelihood of rebleeding. With increased awareness of the effects of Hp infection, the etiologies of bleeding peptic ulcers have shifted to NSAID use, old age, and disease comorbidity.